Misfolding of HLA-B27 as a result of its B pocket suggests a novel mechanism for its role in susceptibility to spondyloarthropathies. - Mear, J; Schreiber, K; Münz, C; Zhu, X; Stevanović, S; Rammensee, H; Rowland-Jones, S; Colbert, R (1999)
The MHC class I protein HLA-B27 is strongly associated with susceptibility to spondyloarthropathies and can cause arthritis when expressed in rats and mice, implying a direct role in disease pathogenesis. A prominent hypothesis to explain this role suggests that the unique peptide binding specificity of HLA-B27 confers an ability to present arthritogenic peptides. The B pocket, a region of the peptide binding groove that is an important determinant of allele-specific peptide binding, is thought to be critical for arthritogenicity. However, this hypothesis remains unproven. We show that in addition to its role in peptide selection, the B pocket causes a portion of the pool of assembling HLA-B27 heavy chains in the endoplasmic reticulum to misfold, resulting in their degradation in the cytosol. The misfolding phenotype is corrected by replacing the HLA-B27 B pocket with one from HLA-A2. Our results suggest an alternative to the arthritogenic peptide hypothesis. Misfolding and its consequences, rather than allele-specific peptide presentation, may underlie the strong link between the HLA-B27 B pocket and susceptibility to spondyloarthropathies.